The Lushai in Tripura ; A Case study - LALTHANNGURI SAILO (IJRDO - Journal of Social Science and Humanities Research, 2022)
The term “ Lushai “ in the correct transliteration of the term ‘Lusei” who were the dominant tribes in the present Mizoram when the British intervened into the then Lushai Hills. To the outsider, the term Lushia in Tripura is almost synonumous with the dweller of the Jampui Hills in the eastern boundary of Tripura. The History of the Lushai in Tripura covers atleast a span of two centuries. However, As much as their Lushai brethen in other parts of India. The Lushai of Tripura have been experiencing changes and facing influences both from internal and external factors in their own context. Major migration of the Lushai from Mizoram had taken place atleast four times ,but when did the first two phase of migration took place were still not ascertained till date. How ever the third and fourth migration took place in about 1900 and 1910 under the leadership of two Sailo Chiefs, Rajabahadur Dokhuma Sailo and Raja Hrangvunga Sailo respectively. Linguisticcally, the Lushai belong to the Tibeto-Burman group and Racially, They belong to the Mongoloid racial stock. In Tripura they are 5,384 person (as per 2011 census). Their Culture is akin to the Mizos. Lushia mostly reside in Jampui Hills area of Tripura. They are an integral part of Tripuras Culture landscape, Particularly in the Jmapui Hills area of North Tripura District. They are also known as Mizo and belong to the Kuki –Chin group of tribes.